Effectiveness of Discovery Learning with Genially for Improving Students’ HOTS Science Literacy on Chemical Bonding - Deka Agustini Laia; Iis Siti Jahro (Jurnal Inovasi Pembelajaran Kimia, 2026)
Higher Order Thinking Skills (HOTS) and scientific literacy are important competencies for students in learning chemistry, especially on abstract topics such as chemical bonding. This study aims to determine the effect of the Discovery Learning model assisted by interactive Genially media on students’ HOTS scientific literacy skills. The study was conducted on 10th grade students at SMA Negeri 2 Percut Sei Tuan on the topic of chemical bonding. This research employed a quantitative pre-experimental method using a one-group pretest-posttest design. The sample consisted of 30 students selected through random sampling techniques. Data were collected using pre-test and posttest instruments designed to measure students’ HOTS scientific literacy skills before and after the implementation of the Discovery Learning model with Genially media. Data analysis included normality tests, paired sample t-tests (right-tail), and N-Gain analysis. The results showed that the average score increased from 34.4 in the pre-test to 59.8 in the post-test. The paired sample t-test produced a significance value of 0.002 (p < 0.05), indicating that the treatment had a significant effect on students’ HOTS scientific literacy skills. In addition, the N-Gain score of 0.34 indicated a moderate level of improvement. In conclusion, the Discovery Learning model assisted by interactive Genially media is effective in improving students’ HOTS scientific literacy skills on chemical bonding.